WHICH TYPE OF PHYSICAL ACTIVITY SHOULD BE RECOMMENDED IN CHILDHOOD OBESITY CONSIDERING VERTEBRAL CURVES AND MOTOR SKILLS? EXERCISE OR SPORTS? - Topcu, Zehra Guchan; Ulger, Ozlem (Stellenbosch Univ, 2022)
This paper aims to compare the effects of functional exercises and basketball training on forward head posture, lumbar hyperlordosis, and motor skills of 45 obese children aged 10 years with forward head posture and hyperlordosis. The children were randomly included to the functional exercise, basketball and control groups for 12 weeks. The angles of lumbar lordosis and craniovertebral were recorded as Form (BOTMP-BF) was used to determine motor skills of the children. Forty-two children completed the study. All groups had similar angles for lumbar lordosis after 12 weeks (p > 0.05), whereas craniovertebral angle significantly decreased in the control group only (p < 0.05). Both functional exercise and basketball were effective in improving speed and agility. There was a statistically significant increase in the total BOTMP-BF score of the functional exercise group (p < 0.001). Both types of physical activity may be a way of managing the progression of forward head posture, whereas they did not affect lumbar posture. Functional exercises and basketball affected different aspects of motor skills.
Keywords: Childhood obesity; Basketball; Exercise